The sowing season : a novel - Powner, Katie (Bethany House, 2020)
"After he's forced to sell the family farm he's labored on his whole life, 63-year-old Gerrit Laninga doesn't know what to do with himself. He sacrificed everything for the land--his time, his health, his family--with nothing to show for it but bitterness, regret, and two grown children who want nothing to do with him. Fifteen-year-old Rae Walters has growing doubts and fears about The Plan--the detailed blueprint for high school that will help her follow in her lawyer father's footsteps. She's always been committed to The Plan, but now that the pressure to succeed is building, what was supposed to unite her family in purpose, may end up tearing it apart. When their paths cross just as they each need a friend the most, Gerrit's and Rae's lives begin to change in unexpected ways. Can they discover together what really matters in life and learn it's never too late for a second chance?"--Provided by publisher.